A New Entry to Purely Organic Thermally Activated Delayed Fluorescence Emitters Based on Pyrido[2, 3‐b]pyrazine‐Dihydrophenazasilines Donor‐Acceptor Dyad. Issue 3 (19th February 2022) - Goya, Tsuyoshi; Zimmermann Crocomo, Paola; Hosono, Takumi; Minakata, Satoshi; de Sousa, Leonardo Evaristo; de Silva, Piotr; Data, Przemyslaw; Takeda, Youhei
Abstract: A new family of thermally activated delayed fluorescence (TADF) emitters based on a twisted donor‐acceptor (D−A) dyad scaffold comprising of dihydrophenazasiline (D) and pyrido[2, 3‐ b ]pyrazine (A) has been developed, and their properties have been investigated. Time‐resolved spectroscopic analysis in matrices revealed the detailed photophysical properties of the D−A compounds. These D−A compounds serve as the emitter for organic light‐emitting diodes (OLEDs), showing a moderate external quantum efficiency (EQE) up to 9% in CBP matrix. Furthermore, theoretical calculations uncovered the excited states nature of the developed TADF emitters. Abstract : A new family of twiste d donor‐acceptor type thermally activated delayed fluorescence (TADF) emitters comprising of pyrido[2, 3‐ b ]pyrazine as the acceptor and dihydrophenazasilines as the donor has been developed. The organic light‐emitting diodes fabricated the developed emitters achieved a high external quantum efficiency up to 9%. Theoretical calculations implied the intermediacy of a high triplet excited state for efficient TADF.